2014
DOI: 10.1158/1078-0432.ccr-13-2958
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Driven Gene Expression Is an Independent Prognostic Factor in Stage II and III Colon Cancer Patients

Abstract: Purpose: Hypoxia is considered a major microenvironmental factor influencing cancer behavior. Our aim was to develop a hypoxia-based gene score that could identify high and low risk within stage II and III colon cancer patients.Experimental Design: Differential gene expression of CaCo-2 colon cancer cells cultured in chronic hypoxia versus normoxia was tested for correlation with prognostic variables in published microarray datasets. These datasets were further used to downsize and optimize a gene score, which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Multiple clinical studies in prostate cancer have reported an association between hypoxia and poor clinical outcome in patients with various types of cancer following chemotherapy or surgery (1, 2). A study of 247 prostate cancer patients with localized intermediate-risk disease showed that tumor hypoxia is associated with early biochemical relapse and local recurrence in the prostate gland (3).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple clinical studies in prostate cancer have reported an association between hypoxia and poor clinical outcome in patients with various types of cancer following chemotherapy or surgery (1, 2). A study of 247 prostate cancer patients with localized intermediate-risk disease showed that tumor hypoxia is associated with early biochemical relapse and local recurrence in the prostate gland (3).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using an in vivo gene-tagging method, it was demonstrated that tumor cells in hypoxic regions could be the origin of recurrence after radiotherapy [8]. It was also reported that change of gene expression in chronic hypoxia was associated with high recurrence rates in colorectal cancer patients [9]. Investigating the biology of tumor cells in hypoxic conditions might be critical for improving therapeutic efficacy and for eradication of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…We used the following existing gene expression signatures for predicting rectal cancer outcomes: the Ghadimi et al 54-gene signature, the Watanabe et al 33 gene signature and the Kim et al 95 gene signature [1820]. Next, we added an Epithelial-to-Mesenchymal (EMT) signature and a hypoxia signature for colorectal cancer [23,24]. Finally, a five-gene signature for predicting metastasis of colorectal cancer was applied [25].…”
Section: Methodsmentioning
confidence: 99%